Transformasi Digital Sistem Pelayanan Pembuatan Surat Keterangan di Desa Cileunyi Wetan - Supriatna, Encep; Aulia, Syifa (Jurnal Accounting Information System (AIMS), 2024)
The Cileunyi Wetan Village Office is a village service center in activities such as governance, empowerment, development and counseling. The Certificate Making Service System in Cileunyi Wetan Village is currently still done manually, that is, people have to come directly to the village office on working days and hours. A system like this is not only very inconvenient for officers because they have to input data every time an application is made, it is also inconvenient for residents because they have to queue and wait for a long time. Moreover, if on the day in question the village head is unable to attend/is away on duty, then the service will be delayed. The digital transformation of the certificate making service system is carried out using the object oriented analysis design model Rational Unified Process (RUP) method with the stages of Inception, Elaboration, Construction and Transition. This system was built using website-based PHP language so that it is easily accessed by village residents from wherever they are provided there is internet access. This digital transformation of the certificate making service system was carried out with the aim of optimizing the village service system for the community in the Cileunyi Wetan Village environment who need a certificate from the village according to the requirements mentioned above. The results showed that with this digital system, apart from being able to help make the work of village officials more effective, it can also increase effectiveness and make it easier for the community to submit the certificates they need.